Psychosocial Correlates of Adolescent Drug Dealing in the Inner City: Potential Roles of Opportunity, Conventional Commitments, and Maturity - Little, Michelle (Journal of research in crime and delinquency, 2006)
This study examined a model of the simultaneous and interactive influence of social context, psychosocial attitudes, and individual maturity on the prediction of urban adolescent drug dealing. Five factors were found to significantly increase adolescents' opportunity for drug selling: low parental monitoring, poor neighborhood conditions, low neighborhood job opportunity, parental substance use or abuse, and high levels of peer group deviance. The relation between drug selling opportunity and adolescents' frequency of drug selling was partially mediated by adolescents' alienation from conventional goals and from commitment to school. With the effect of drug-dealing opportunity controlled, adolescents' temperance was associated with a lower frequency of drug selling. Youths with greater resistance to peer influence reported a higher frequency of nonmarijuana drug dealing. Adolescent autonomy also predicted adolescents' nonmarijuana dealing in conditions of low drug selling opportunity. The results are discussed with respect to the social service needs of serious juvenile offenders. [ABSTRACT FROM AUTHOR]